Physical fitness and wellness : changing the way you look, feel, and perform - Greenberg, Jerrold S.; Dintiman, George B.; Myers Oakes, Barbee (United States : Human Kinetics, 2004)
his comprehensive text aims to provide students with the information, strategies & motivation they need to help themselves improve the way they look, feel & perform.
Includes bibliographical references and index.
Keywords: Physical fitness; Health; Exercise